Sistemas agroflorestais e a construção do conhecimento agroecológico em assentamentos rurais - Nobre, Henderson Gonçalves (Universidade Federal de São Carlos, 2011)
The Sepé Tiaraju, the first one settlement in the mode of Sustainable Development Project PDS of São Paulo state, founded in 2004 in the sugarcane region of Ribeirão Preto/SP, has as a proposal being an alternative to the conventional forms of land occupation and management of natural resources adopted in the region. Then a group of farmers along with Embrapa Environment, INCRA/SP and other partners has been trying to consolidate a participative strategy of development and generation of agro-ecological knowledge in the settlement using Agroforestry SAFs. Based on this ongoing process in the Sepe Tiaraju settlement, this study uses methodologies such as Participatory Rural Appraisal, Participatory Action Research and Participant Observation to analyze the strategies of development adopted, and the contribution of the SAFs for the construction of agro-ecological knowledge and the consolidation of sustainable production systems. In summary we can say by this study that the Agroecology and the use of participative methodologies are essential to conduct local development strategies, thereby promoting the construction, validation and appropriation of knowledge by farmers. It also became clear the contribution of the agroforestry to conciliate the environmental conservation with the diversified food production for the families selfconsumption and even surplus for commercialization and income generation.
Agroforestry systems and agro-ecological knowledge construction in rural settlements
Keywords: Agroecologia; Sistemas agroflorestais; Metodologias participativas; Agricultura familiar; Sustentabilidade; Agroecology; Agroforestry systems; Participative methodologies; Family agriculture; Sustainability; CIENCIAS AGRARIAS